Ekonomski in pravni pogled na prirejanje spletnih iger na srečo - zakaj je monopol lahko boljši kot prosti trg - Zajc, Katarina (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2011)
Together with the development of technology, the on-line gambling expanded all over the world, together with hunger for income and unfortunate appearance of negative effects connected with gambling - negative externalities. With high incomes and big negative externalities the question arises whether or not and to what extent the regulation of internet gambling is beneficial. The article first discusses EU and Slovenian regulation of internet gambling by discussing the European Court of Justice cases in the gambling field and the adherence of Slovenian regulation to the ECJ decisions. The second part of the article examines the economic rationale of ECJ gambling decisions and concludes that the ECJ decisions make economic sense, since they intend to increase the welfare in society. The article concludes that the monopoly in the internet gambling sector might be more beneficial for the economy than the competition.
Keywords: competition; European Union; Evropska unija; igre na srečo; monopoly; on-line gambling; svetovni splet; spletni portali; European Court of Justice; efficiency; trg; monopol; Christoph Andersson; konkurenca; spletne igre na srečo; Sodišče Evropske unije; učinkovitost